2022
DOI: 10.3390/biom12091233
|View full text |Cite
|
Sign up to set email alerts
|

t6A and ms2t6A Modified Nucleosides in Serum and Urine as Strong Candidate Biomarkers of COVID-19 Infection and Severity

Abstract: SARS-CoV-2 infection alters cellular RNA content. Cellular RNAs are chemically modified and eventually degraded, depositing modified nucleosides into extracellular fluids such as serum and urine. Here we searched for COVID-19-specific changes in modified nucleoside levels contained in serum and urine of 308 COVID-19 patients using liquid chromatography-mass spectrometry (LC-MS). We found that two modified nucleosides, N6-threonylcarbamoyladenosine (t6A) and 2-methylthio-N6-threonylcarbamoyladenosine (ms2t6A), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…RNA nucleoside mass spectrometry was performed as previously described in refs. 45 47 . A 25 μL solution containing 3 μg of heart total RNA, 20 mM Hepes-KOH (pH 7.6), 2 units of Nuclease P1 (Fujifilm, Tokyo, Japan), and 0.25 units of bacterial alkaline phosphatase (Takara, Kusatsu, Japan) was incubated at 37 °C for 3 h. About 3 μL of the nucleoside solution was then injected into the LC-MS-8050 system (Shimadzu, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…RNA nucleoside mass spectrometry was performed as previously described in refs. 45 47 . A 25 μL solution containing 3 μg of heart total RNA, 20 mM Hepes-KOH (pH 7.6), 2 units of Nuclease P1 (Fujifilm, Tokyo, Japan), and 0.25 units of bacterial alkaline phosphatase (Takara, Kusatsu, Japan) was incubated at 37 °C for 3 h. About 3 μL of the nucleoside solution was then injected into the LC-MS-8050 system (Shimadzu, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Through liquid chromatography–mass spectrometry (LC-MS) analysis of biological samples, the researchers proposed the potential utility of m 6 t 6 A and t 6 A as diagnostic biomarkers for COVID-19. Furthermore, the study demonstrated a positive correlation between the severity of COVID-19 and elevated levels of serum ms 2 t 6 A, suggesting the prognostic value of this RNA modification as a predictive marker for coronavirus infection [ 156 ].…”
Section: Discussionmentioning
confidence: 99%